Effect of plant growth promoting Rhizobacteria (PGPRS) on yield and quality of processing tomato under water deficiency - Andryei, Bulgan; Horváth, Kitti Zsuzsanna; Ráth, Szilvia; Nemeskéri, Eszter; Neményi, András; Pék, Zoltán; Helyes, Lajos (Acta Agraria Debreceniensis, 2020)
Chlorophyll fluorescence was measured of H1015 tomato hybrid with different bacterial treatments (B0–B1–B2–B3) and three irrigation treatments: regular irrigated (RI), deficit irrigated (DI) and non-irrigated conditions (I0). The aim of the experiments was to show the effects of plant growth promoting rhizobacteria on the yield, dry matter and vitamin C content of processing tomato during different irrigation treatments, and measuring the chlorophyll fluorescence during the ripening and development stages. According to the results, none of the bacterial treatments had a statistical effect on the quantity and quality of the tomato and on the chlorophyll fluorescence, only the irrigation. Further studies are needed.